516 THE CHARACTERIZATION OF DYSPLASIA IN BARRETT'S ESOPHAGUS—A PROSPECTIVE NATIONWIDE REGISTRY FROM THE RIBBON NETWORK. (14th September 2020) - O Byrne, L; O' Brien, M; Muldoon, C; Ryan, C; Buckley, M; Murphy, T; Reynolds, R; Patchett, S; Kay, E; Azam, H; Robb, W; Arumugasamy, M; et al.
Abstract: : Barrett's Esophagus is the main pathological precursor to esophageal adenocarcinoma (EAC), dysplasia is known to be one of the principal predictors of progression to malignancy. The RIBBON Registry was established with six academic medical centers in the Republic of Ireland to identify and manage high risk Barrett's Esophagus (BE) patients. From our database of over 4, 000 patients our aim was to establish characteristics of those patients who progressed to dysplasia and furthermore to malignancy. Methods: Data was gathered prospectively from December 2007—December 2019. Ethical approval was sought for the database at the time of establishment. Detailed endoscopic, pathological and clinical data was collected via a web-based data capture system at time of initial diagnosis and at each subsequent encounter. A data manager was appointed at each site and a national lead coordinating the project. The Vienna Grading system was used to grade histology. Patients were included if they had an initial or subsequent diagnosis of Specialized intestinal metaplasia (SIM), Indefinite for dysplasia (IND) or Low-Grade Dysplasia (LGD). Results: 860 patients were included with a total of 3792 patient years, a male to female ratio of 2.9:1 and a median age at diagnosis of 63. 50 patients had an initial diagnosis of SIM with subsequent episodes of dysplasia while 510 patients had IND or LGD at diagnosis. 158 (18.37%) progressed to High grade dysplasia (HGD) and EAC. The overall incidence of EAC was 1.7% per year, HGD 2.4% per year and a combined rate of 4.2% per year. Median time to progression in SIM was 4.7 years, 1.1 years for IND and 9 months for LGD. Conclusion: The overall progression of the group was much higher compared to looking at those who had SIM alone without dysplasia from the same registry (0.9% per year). Time to progression was significantly faster in the groups with initial dysplasia be that IND or LGD. In our centers those patients were followed up with repeat endoscopy as per international guidelines, the above results highlight the importance of this practice given the potential for malignancy.